What determines the corporate capital structures? Evidence from emerging markets in the light of the Asian financial crisis - Hamouda, Raja Zekri Ben; Souffargi, Wafa; Jilani, Faouzi (Asian Economic and Financial Review, 2025)
The purpose of this paper is to identify and study the most relevant factors that explain the debt-equity choices of firms in emerging markets. Using data from 4,735 non-financial listed firms from 18 emerging markets over the "special" period 1990-2007, results indicate that asset tangibility, firm size, private credit to GDP, and the creditor protection index are associated with higher leverage ratios, while profitability, growth opportunities, the shareholder protection index, stock market size, the legality index, GDP growth rate, and inflation rate are associated with lower leverage ratios. Using the panel data approach, results also indicate that the tangibility of assets and the shareholder rights index are the most prominent determinants of capital structure. Furthermore, the research suggests that the debt-equity choice decisions of firms differ according to geographical origin, legal origin, and financial system development. Differences also exist at the sectoral level. Results finally show that the Asian financial crisis had effects on capital structure determinants. We detect significant upward trends in four different leverage ratios before and during the eruption of the financial and banking crisis. After the crisis, asset tangibility, profitability, and the creditor rights index influence the firm’s capital structure determinants differently.